Проблема транспортировки каспийской нефти с точки зрения национальных интересов Украины - Ксензенко, В. (Социология: теория, методы, маркетинг, 1999)
Caspian oil is à point of our interest mostly due to the intensifying geopolitical fightfor the oil resources which are of strategic importance not only in the regional sense but in the whole world. The problem is relevant to the national interests of Ukraine because the country tends to the oil supply diversification and Caspian oil transportation ways, in particularly, the renewed historical Silk Way.